Analisis Continuace Intention Penggunaan Aplikasi Ikisi untuk Investasi Saham Syariah Berdasarkan Model Unified Theory of Acceptance and Use of Technology (UTAUT) (Studi Kasus Investor Ikisi di Kota Bengkulu) - Wulan Sumarni; Evan Stiawan; Yetti Afrida Indra (Universitas Muhammadiyah Surabaya, 2026)
This study aims to measure and analyze the influence of performance expectancy, effort expectancy, social influence, and facilitating conditions on the continuance intention of users of the iKISI application for sharia stock investment. The population in this study consists of iKISI investors. The method used is quantitative. The data used in this research are primary data obtained through the distribution of questionnaires to 96 investor respondents and analyzed using multiple linear regression analysis with the assistance of SPSS version 31.The results show that partially, performance expectancy and social influence do not have a significant effect on the continuance intention of iKISI application users. In contrast, effort expectancy and facilitating conditions are proven to have a positive and significant effect on continuance intention. Simultaneously, the four independent variables significantly influence continuance intention. The Adjusted R Square value of 0.265 indicates that the variables of performance expectancy, effort expectancy, social influence, and facilitating conditions are able to explain 26.5% of the variation in continuance intention, while the remaining percentage is influenced by other variables outside the research model.These findings indicate that the ease of using technology and the availability of supporting system facilities are important factors in encouraging the continued use of the iKISI application for sharia stock investment.